Surfactin inhibits the growth of Propionibacterium acnes by destroying the cell wall and membrane. (1st December 2021) - Shan, M.Y.; Meng, F.Q.; Zhou, L.B.; Lu, F.X.; Bie, X.M.; Zhao, H.Z.; Lu, Z.X.
Abstract: Propionibacterium acnes plays a major role in acne vulgaris. In the pre‐experiment, the growth of P. acnes was inhibited effectively using surfactin; however, the antibacterial mechanism has not been described. Therefore, the aim of this study was to evaluate antibacterial activity and analyse the mechanism of surfactin against P. acnes . Minimum inhibitory concentration, time‐killing kinetics and scanning electron microscopy were used to evaluate the activity of surfactin against P. acnes, which showed that 128 μ g ml −1 effectively inhibited growth. Cell wall permeability was evaluated by detecting the extracellular alkaline phosphatase activity, which increased to 1·83‐ and 2·32‐fold after incubating with 128 and 256 μ g ml −1 of surfactin for 10 h, respectively. Propidium iodide fluorescence, leakage of nucleic acid, protein, K +, and Ca 2+, membrane potential and the leakage of calcein from small unilamellar vesicles all increased after incubation with surfactin, indicating that its strong biological activities act mainly by altering membrane integrity. In a mouse model of acne, surfactin significantly reduced P. acnes –induced epidermal swelling and erythema. These results indicate that surfactin effectively inhibited the growth of P. acnes by destroying the cell wall and membrane, and is a potential candidate for acne treatment.